One Versus Two Doses of Intravenous Tranexamic Acid in Total Knee Arthroplasty - Charette, Ryan S.; Bernstein, Jenna A.; Sloan, Matthew; Nchako, Corbyn M.; Kamath, Atul F.; Nelson, Charles L. (The Journal of Knee Surgery, 2019)
Tranexamic acid (TXA) has been shown to reduce blood loss and postoperative transfusions in total knee arthroplasty (TKA). There is no consensus on the ideal dosing regimen in the literature, although there is a growing body of literature stating there is little benefit to additional doses. Our study compared one versus two doses of TXA in primary TKA and its effect on postoperative transfusion rate. We retrospectively reviewed patients undergoing primary TKA at our two high-volume arthroplasty centers between 2013 and 2016. Patients were included if they underwent unilateral primary TKA, and received one or two doses of intravenous TXA. Patients receiving therapeutic anticoagulation were excluded. Our primary outcome was postoperative transfusion rate. Secondary outcomes included blood loss, length of stay, rate of deep vein thrombosis or pulmonary embolism (DVT/PE), readmission and reoperation.A total of 1,191 patients were included: 891 received one dose and 300 received two doses. There was no significant difference in rate of transfusion, deep vein thrombosis or pulmonary embolism (DVT/PE), blood volume loss, and reoperation. There was a significantly higher risk of readmission (6.7 vs. 2.4%, odds ratio [OR] 2.96, p < 0.001) and reoperation (2.0 vs. 0.6%, OR 3.61, p = 0.024) in patients receiving two doses. These findings were similar with subgroup analysis of patients receiving only aspirin prophylaxis.In unilateral TKA, there is no difference in transfusion rate with one or two doses of perioperative TXA. There was no increased risk of thromboembolic events between groups, although the two-dose group had a higher rate of readmission and reoperation. Given the added cost without clear benefit, these findings may support administration of one rather than two doses of TXA during primary TKA.
Keywords: total knee arthroplasty; tranexamic acid; blood transfusion